LOW ACADEMIC PERFORMANCE: CONTEXT AND CHALLENGES - Kumar, Sunil; Kumar, Alok (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This research paper is written on the low academic performance in the school of students studying in the middle stage. Efforts are being made to improve the academic performance of the children through various programs at the school level, yet the low academic performance of the students remains a challenge for parents and teachers. At present this issue needs to be understood with great sensitivity. Through this research paper the authors have studied the low performing students and their teachers at the school level and by analyzing the references of all the partners discuss the causes and effective solutions related to this issue. This research paper can help the policy makers, teachers and researchers working in this field to better understand the concerns of low academic performance and find the necessary solutions. The main results of the research found that the poor financial status of the students' families, active participation of children in household chores, lack of awareness of punishment and punishment by parents, family tension, and drug habits etc. are the causes of low academic performance. Other reasons for low academic performance include lack of concentration in the classroom, lack of interest in learning and lack of coordination with teachers.